Pengembangan Instrumen Penilaian Apresiasi Cerpen Berbasis Penggunaan Website dan Spreadsheet untuk Siswa SMA - Qonita Sumardani; Tifany Diahnisa; Raiyan Armansa Putra; Sarwiji Suwandi (Universitas Pendidikan Mandalika, 2022)
This study aims to develop a short story appreciation assessment instrument using the Ruang Sastra Website and Spreadsheet for high school students. This study used the Research and Development method from Borg and Gall. The subjects in this study were teachers and high school students. The data used are qualitative and quantitative, with data collection techniques through questionnaires distributed to teachers and students online using Google Forms, interviews with teachers, and expert validation. The data analysis technique in this study was in the form of descriptive analysis of scores obtained from the validation results of experts, practitioners, and response questionnaires. The results of this study indicated that developing a short story appreciation assessment instrument based on websites and spreadsheets for high school students was feasible in terms of exploratory studies, development of assessment instrument designs, and expert validation tests.